Efektivitas dan kontribusi retribusi tempat rekreasi dan olahraga terhadap pendapatan asli daerah di Kabupaten Sinjai - Fauziah; Sri Nirmala Sari; Imron Burhan (PT Bone Jaya Kreatif, 2022)
The purpose of this study are to determine the effectiveness and contribution of levy for recreation. and sports to local revenue in Sinjai Regency. This study used descriptive data analysis techniques. The research data is secondary data in the form of data on the realization of levy for recreation and sports, targets for retribution for recreation and sports as well as data on the realization of local revenue in Sinjai Regency. The results show that the effectiveness of the levy for recreation and sports in Sinjai Regency in 2016 and 2017 are classified as less effective, while in 2018 and 2019 it are is very effective. The contribution of levy for recreation and sports to the local revenue of Sinjai Regency in 2016 to 2019 is less effective.